Training Rats to Voluntarily Dive Underwater: Investigations of the Mammalian Diving Response - McCulloch, Paul F. (J Vis Exp, 2014)
Underwater submergence produces autonomic changes that are observed in virtually all diving animals. This reflexly-induced response consists of apnea, a parasympathetically-induced bradycardia and a sympathetically-induced alteration of vascular resistance that maintains blood flow to the heart, brain and exercising muscles. While many of the metabolic and cardiorespiratory aspects of the diving response have been studied in marine animals, investigations of the central integrative aspects of this brainstem reflex have been relatively lacking. Because the physiology and neuroanatomy of the rat are well characterized, the rat can be used to help ascertain the central pathways of the mammalian diving response. Detailed instructions are provided on how to train rats to swim and voluntarily dive underwater through a 5 m long Plexiglas maze. Considerations regarding tank design and procedure room requirements are also given. The behavioral training is conducted in such a way as to reduce the stressfulness that could otherwise be associated with forced underwater submergence, thus minimizing activation of central stress pathways. The training procedures are not technically difficult, but they can be time-consuming. Since behavioral training of animals can only provide a model to be used with other experimental techniques, examples of how voluntarily diving rats have been used in conjunction with other physiological and neuroanatomical research techniques, and how the basic training procedures may need to be modified to accommodate these techniques, are also provided. These experiments show that voluntarily diving rats exhibit the same cardiorespiratory changes typically seen in other diving animals. The ease with which rats can be trained to voluntarily dive underwater, and the already available data from rats collected in other neurophysiological studies, makes voluntarily diving rats a good behavioral model to be used in studies investigating the central aspects of the mammalian diving response.